Influence of Knowledge of Smoking as Cancer-Causing on Behavior among Smokers - Ahram, Mamoun; Alshiyyab, Reem; Al Debie, Ashraf; Al-Sukhni, Ala’a; Shabsough, Asma; Jaghbir, Madi (Jordan Medical Journal, 2023)
Background: Smoking-related behavior including passive smoking poses a major burden on the health status of populations and national economies. This is particularly true for countries that have a high prevalence of smoking like Jordan, which also has an increasing trend of waterpipe smoking: Knowledge of passive smoking and the association of knowledge of smoking as cancer-causing with quitting in addition to characteristics of smokers with denial or ignorance were assessed. Methods: This study is part of a nationwide, cross-sectional survey conducted in Jordan. Respondents (3196) were asked about their knowledge of passive smoking in addition to the association of active, waterpipe, and passive smoking with cancer. Smokers were also asked about the possibility of them developing cancer. Knowledge and perception were correlated to past attempts and future intentions of quitting smoking. Smokers with a denial of developing cancer or lack of knowledge of the association of smoking with cancer were further characterized. Results: Approximately half of the respondents, in general, knew of the term “passive smoking.” Knowledge of the association of smoking-related behavior with cancer was very high ( 95%). However, almost 75% of smokers thought that they would develop cancer with a strong association between this perception with previous attempts or future intentions to quit smoking. Whereas smokers in their 20s and 50s, those with decreasing income, and female smokers were more likely to be in denial that they may develop cancer, male smokers and smokers in their 40s, or with intermediate education or increasing income appeared to be ignorant of the association of smoking with developing cancer. Conclusions: These results may aid in the development of more effective and targeted anti-smoking campaigns.